Employee Engagement in Job Transfer Practices at The Directorate General of Customs and Excise, Ministry of Finance, Republic of Indonesia - Harwan Ony Prasetyanto; Fendy Suhariadi; Sri Pantja Adyawati; Novita; Umar Haidar Faizurrahman; Abu Bakar Mujahid; Rian Pramana Suwanda (Airlangga Development Journal, 2026)
This study aims to analyze the dynamics of employee engagement among employees of Directorate General of Customs and Excise (DJBC) within the homebase and nonhomebase job transfer system. The study is motivated by the high mobility of DJBC employees, which not only contributes to organizational competency development but also generates various psychological, social, and economic consequences for employees. This research employed a qualitative approach using a case study method. Data were collected through observations, in-depth interviews, and documentation involving 37 informants selected through purposive sampling techniques. Data analysis was conducted using a grounded theory-informed analysis approach through the stages of open coding, axial coding, and selective coding. The findings reveal that homebase transfers tend to produce higher levels of employee engagement as they provide emotional stability, family proximity, and better work-life balance. In contrast, non-homebase transfers, although offering opportunities for new experiences, learning, and competency development, are more likely to create psychological pressure, family conflicts, financial burdens, and decreased work motivation, which subsequently weaken employee engagement. The study also found that factors such as supportive leadership, harmonious work environments, certainty in transfer rotation patterns, work flexibility, and fair and transparent organizational policies significantly influence employees’ attachment to the organization. Furthermore, employees’ perceptions of job transfers are strongly shaped by the personal meanings attached to the transfer process, particularly regarding organizational appreciation, career promotion, and perceptions of fairness. This study reinforces the relevance of Social Exchange Theory (SET), Organizational Justice Theory, Self Determination Theory (SDT), and Conservation of Resources Theory (COR) in explaining employee engagement dynamics within public sector job transfer systems. The findings also confirm that work-life balance is the most dominant factor in maintaining employee engagement under job transfer arrangements. Therefore, organizations need to develop more adaptive, flexible, and human-centered transfer policies through the implementation of Flexible Working Arrangements (FWA), transfer support facilities, clear placement rotation systems, and supportive leadership practices to sustain employee engagement and organizational performance in the long term.